Novel Technique to Reconstruct Peri-Implant Keratinised Mucosa Width Using Xenogeneic Dermal Matrix. Clinical Case Series - Attila Horváth; Péter Windisch; Dániel Palkovics; Xinda Li (MDPI AG, 2024)
Reconstruction of sufficient buccal peri-implant keratinised mucosa width (PIKM-W) is reported to reduce the symptoms of peri-implantitis. In order to reduce the drawbacks of autogenous graft harvesting, we investigated a novel porcine dermal matrix (XDM, mucoderm®) using a modified surgical technique for augmentation of PIKM-W. Twenty-four patients were recruited with insufficient (<2 mm) PIKM-W. After split thickness flap preparation, the XDM was trimmed, rehydrated and tightly attached to the recipient periosteal bed using modified internal/external horizontal periosteal mattress sutures via secondary wound healing. Change of the PIKM-W and dimension of the graft remodelling were evaluated at 6 and 12 months postoperatively. The mean PIKM-W changed from 0.42 ± 0.47 to 3.17 ± 1.21 mm at 6 M and to 2.36 ± 1.34 mm at 12 M in the maxilla and from 0.29 ± 0.45 mm to 1.58 ± 1.44 mm at 6 M and to 1.08 ± 1.07 mm at 12 M in the mandible. Graft dimensions decreased by 67.7 ± 11.8% and 81.6 ± 16.6% at 6 M, and continued to 75.9 ± 13.9% and 87.4 ± 12.3% at 12 M, in the maxilla and mandible, respectively. Clinical parameters showed statistically significant intra- and intergroup differences between the baseline and 6 and 12 months (p < 0.05). The present technique using the XDM was safe and successfully reconstructed PIKM-W in both arches. The XDM alone seems to be a suitable alternative to autograft for PIKM-W augmentation in the maxilla.